Thing-Thing / [illustrated by] Nicolas Debon. - Fagan, Cary (Tundra Books, 2008)
"Thing-Thing was neither a Teddy bear nor a rabbit; not a stuffed dog or cat. It was something like each of those, and nothing at all you could name. But it had something special. It had hope that one day it would find a child to love it and talk to it and make it tea parties and take it to bed..."--Jacket.